The Brigade Renderer: A Path Tracer for Real-Time Games. (17th March 2013) - Bikker, Jacco; van Schijndel, Jeroen
Abstract : We present the Brigade renderer: an efficient system that uses the path tracing algorithm to produce images for real-time games. We describe the architecture of the Brigade renderer, and provide implementation details. We describe two games that have been created using Brigade.